(untitled) (DAPesquisa, 2020)
The text experiments and reflects on the writing modes of the research of its authors — who investigate creative processes of dramaturgies, vocal poetics and vocal pedagogies. In play of writing, they looking for ways of research and mythodologicals research writings, inspired by the mythical resonances of the imagination. These writings also contemplate experiments in forms commonly placed on the margins of those considered “official” in academic writing, such as letters, poetry, fiction. Drawing on the pages the words and images dictated by the affects and rhythms of their bodies in creative work, the authors also seek to constitute and map feminist poetics and pedagogies in the context of the scene.